Language Contact at the Romance-Germanic Language Border - Treffers-Daller, Jeanine 1959-; Willemyns, Roland 1936- (Multilingual Matters, 2002)
The current volume brings together sociolinguistic analyses of language contact along the Romance Germanic Language Border, shedding more light on the variable and the universal elements in language contact and shift. It covers the whole range of the border, from French Flanders through South Tirol. Every part of it has been treated by outstanding experts. They describe the current state of the art in ‘their' portion of the language border and include information on the legal and/or practical status of the language border and the status and function of all languages concerned. Attitudinal and language planning initiatives as well as the standardisation status of the regionally official and minority languages are discussed. Language borrowing, code switching and other language contact phenomena are analysed in detail
Description based on online resource; title from PDF title page (publisher's Web site, viewed 07. Dez 2018)
Keywords: Germanic languages -- Social aspects; Languages in contact -- Europe; Languages in contact; Romance languages -- Social aspects; Grenzgebiet; Sprachkontakt; Romanische Sprachen; Germanische Sprachen; Europa; Aufsatzsammlung